Pengaruh Modal Dan Keterampilan Terhadap Minat Berwirausaha Mahasiswa STIE Bina Karya Tebing Tinggi - Syafrizal, Rodi (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
Most students only rely on the hope that after finishing college they want to be able to work, not start a business. Because the Indonesian people are more dominant in having the mentality of workers than entrepreneurs, therefore mental improvement is needed so that the Indonesian people can work and be independent through entrepreneurship development. This research was conducted to determine the extent of capital and skills in influencing the interest of STIE Bina Karya Tebing Tinggi students. This study uses a quantitative method approach by using primary data derived from questionnaires which are analyzed using the multiple regression method which is processed in SmartPLS 3. The results of research and discussion on the effect of capital and skills on interest in entrepreneurship it can be concluded that capital and skills have a positive and significant influence on the entrepreneurial interest of STIE Bina Karya Tebing Tinggi where the influence of these two variables is substantial or strong in influencing the entrepreneurial interest of students at STIE Bina Karya Tebing Tinggi.